A Novel Method of the Treatment for Posterolateral Tibial Plateau Fractures - Ren, Dong; Liu, Yueju; Chen, Yanxi; Lu, Jian; Song, Zhaohui; Zhou, Bing; Wang, Pengcheng (The Journal of Knee Surgery, 2019)
Reduction and fixation of posterolateral tibial plateau fracture via a posterolateral approach is challenging, and the posterolateral approach itself may injure the posterolateral ligament complex of the knee and can result in knee instability. We developed a new curved support plate (CSP) that can pass, via traditional anterolateral approach, through the superior tibiofibular interval and effectively support the posterolateral fragments. The purpose of our study was to determine the biomechanical reliability of the new plate and report the preliminary efficacy of the CSP for posterolateral tibial plateau fracture. In the biomechanical experiment, 40 synthetic tibias were used to create posterolateral shearing tibial fracture models, which were randomly assigned to groups A to D. Vertical displacement of the posterolateral fragments was measured under axial loads of 500 to 1,500 N. The new plate and 3.5-mm lateral locking plate exhibited similar control over fragment displacement. From June 2016 to August 2017, eight patients with posterolateral tibial plateau fracture underwent treatment with the CSP. Hospital for Special Surgery (HSS) knee score, knee flexion and extension ranges of motion, and complications were recorded to evaluate treatment effects. Eight patients (five men and three women, mean age 44 years [range, 23–66 years]) were enrolled in the study. Mean follow-up time was 13 months (range, 7–19 months). All patients achieved radiographic bone union by 3.3 months (range, 3–4 months) postoperatively. There were no complications of neurovascular injury, deep vein thrombosis, infection, and implant loosening throughout the follow-up period. At final follow-up, mean HSS score was 92.6 (88–96), with a mean knee flexion of 131.25 degrees (120–135 degrees) and a mean knee extension of 1 degree (0–5 degrees). Fixation of posterolateral tibial plateau fracture was easily and successfully achieved using our newly designed CSP, which may provide a new choice for posterolateral tibial plateau fractures.
Keywords: CSP; anterolateral approach; posterolateral tibial plateau fracture